2019
DOI: 10.37358/rc.19.7.7340
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Known Prognostic Markers and Tumor - infiltrating Lymphocytes in Breast Cancer

Abstract: The presence of tumor-infiltrating lymphocytes (TILs) is associated with a favorable long-term outcome in breast cancer. The main objective of this study was to show that there is a correlation between known prognostic and predictive factors and TILs. We retrospectively identified 56 patients with human epidermal growth factor receptor-2 (HER2 +, n = 22) and HER2 negative (HER2-, n = 34) breast cancer diagnosed between 2012 and 2018 at the Institute of Oncology Prof. Dr. Alexandru Trestioreanu, Bucharest. Hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Recent studies have shown that the therapeutic effect of trastuzumab depends on the acquired and adaptive mechanisms, mediated by immunity. For example, a combination therapy that inhibits the PI3K / AKT pathway for resistance to trastuzumab increases the intratumoral infiltration of T cells, thereby expanding the anti-tumor effect and immune response mediated by CD8 + T cell, thus enhancing the therapeutic effects of the anti-HER2 antibody [19][20].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that the therapeutic effect of trastuzumab depends on the acquired and adaptive mechanisms, mediated by immunity. For example, a combination therapy that inhibits the PI3K / AKT pathway for resistance to trastuzumab increases the intratumoral infiltration of T cells, thereby expanding the anti-tumor effect and immune response mediated by CD8 + T cell, thus enhancing the therapeutic effects of the anti-HER2 antibody [19][20].…”
Section: Resultsmentioning
confidence: 99%
“…It has been showed that both benign and malignant melanocytic lesions are positive for ERβ, but not for ERα, which seems to be very rarely expressed in the skin [20][21]. In line with this observation, various studies support a role for ERβ in contributing to the better survival rates among women [22,23].…”
Section: Hormones and Melanomamentioning
confidence: 92%
“…Inhaled administration of corticosteroids is related only to early miscarriage, a correlation with the late miscarriage hasn't been described yet. This reflects that intrauterine exposure to this medication influences the fetal environment, leading to an increased risk of early pregnancy loss [35][36][37].…”
Section: Inhaled Corticosteroidsmentioning
confidence: 99%